1995
DOI: 10.2307/1602510
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prenatal Care in Preventing Low Birth Weight

Abstract: Prenatal care has long been endorsed as a means to identify mothers at risk of delivering a preterm or growth-retarded infant and to provide an array of available medical, nutritional, and educational interventions intended to reduce the determinants and incidence of low birth weight and other adverse pregnancy conditions and outcomes. Although the general notion that prenatal care is of value to both mother and child became widely accepted in this century, the empirical evidence supporting the association bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(133 citation statements)
references
References 74 publications
4
128
0
1
Order By: Relevance
“…The expected secondary impacts are shown in the second column of Table 3.17. In particular, research has demonstrated the importance of access to prenatal care services for the health of the mother and her child (Alexander and Korenbrot, 1995;Korenbrot et al, 2002;Rossin-Slater, 2015). For low-income women, the provision of subsidized care has been shown to reduce the incidence of low birth weight and lower infant mortality (Currie andGruber, 1996a, 1996b).…”
Section: Expected Effectsmentioning
confidence: 99%
“…The expected secondary impacts are shown in the second column of Table 3.17. In particular, research has demonstrated the importance of access to prenatal care services for the health of the mother and her child (Alexander and Korenbrot, 1995;Korenbrot et al, 2002;Rossin-Slater, 2015). For low-income women, the provision of subsidized care has been shown to reduce the incidence of low birth weight and lower infant mortality (Currie andGruber, 1996a, 1996b).…”
Section: Expected Effectsmentioning
confidence: 99%
“…13 Patients need referrals from their GPs only for consultations with radiologists. 14 For the general role of prenatal care, see e.g., Alexander and Korenbrot (1995). 15 There is a strong financial incentive to take the exams, as eligibility for several family benefits depends on proof of participation.…”
Section: Institutional Setting Data and Estimation Strategymentioning
confidence: 99%
“…Previous evidence showed that maternal weight gain during pregnancy has a positive effect on birth weight of the neonate (Haughton et al, 1992;Alexander and Korenbrot, 1995;Viswanathan et al, 2008). In Bangladesh, National Nutrition Program Baseline Survey 2004 showed that only one-third women had gained more than 4 kg during the third trimester.…”
Section: Introductionmentioning
confidence: 98%